Hubungan Antara Self Regulated Learning Dan Keterampilan Literasi Digital Pada Mahasiswa Universitas Negeri Makassar - Eka Hardiana Suci; Ahmad Razak (CV. Ulil Albab Corp, 2024)
In education, self-regulated learning is one of the achievements that must be met in the learning process. The ability to use digital devices to increase knowledge and achievement is a challenge in the process of self-regulated learning. The lack of digital literacy skills makes students unable to fulfill their learning needs. The purpose of this study was to determine the relationship between self-regulated learning and digital literacy skills in students of Universitas Negeri Makassar. The subjects in this research were taken using accidental sampling technique, namely 600 students. The hypothesis of this research was tested using the Spearman's rho correlation test. The results showed that the significance value of p = 0.000 (p <0.05), and the correlation coefficient r = 0.441, which means that there is a positive relationship between self-regulated learning and digital literacy skills which is significant with a strong correlation.